GEOELECTRICAL SURVEYS IN THE OL'KHON REGION: METHODS, RESULTS, AND TECTONIC IMPLICATIONS - Kozhevnikov N.O.; Bigalke J.; Kozhevnikov O.K. (My University, 2004)
The paper presents the results of SP, TEM, and VLF surveys in the Olkhon region along two 6 and 11.5 km profiles which traverse major two-dimensional tectonic structures. The region is divided into a northwestern and a northeastern tectonic blocks separated by the Kuchulga fault. The northwestern (Chernorud) block is marked by a negative SP anomaly of hundreds millivolt coinciding with a flat electrical conductor detected by TEM soundings at depths between 120 and 450 m. The SP anomaly may be produced by a natural galvanic cell (a geobattery) in which electronic conductive graphite mineralization connects regions of different redox potentials in an electrolytic formation. The tectonic origin of the anomaly remains unclear and may be associated with shearing, mylonitization, and plastic flow in a regional-scale low-angle thrust. The southeastern block confined between the Kuchulga fault and the Baikal shore is geoelectrically uniform and tectonically much more stable than the Chernorud block. Horizontal conductors in the southeastern block were never observed before but may be expected to appear in TEM records from greater-moment sources and/or in MT data.
Keywords: Geoelectrical surveys; SP; TEM; geobattery; conductor; tectonics; Ol'khon region